The Study of Learning Islamic Religious Education (PAI) Based on Contextual Teaching and Learning in MA Darul Iman in Pamolaan Village Camplong Sampang - mu awah (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2017)
Muawah (2017), “The Study of Learning Islamic Religious Education (PAI) Based on Contextual Teaching and Learning in MA Darul Iman Pamolaan Village Camplong Sub district Sampang Regency”. Keywords: Learning ( Islamic Religious Education), Contextual Teaching And Learning The quality of life of the nation is determined by education factor. The role of education is very important to create a smart, peaceful, and democratic life. Religious education should be used as a benchmark in shaping the character and personality of learners, and build nation's character (nation character building). So in practice, religious education (Islam) should be carried out as well as possible with mature management and directed to the continuity of human relationships with His creator, human with human (society) and human with environmant. The researcher describes the formulation of the problem from this research as follows: First How is the planning of Islamic education based on Contextual Teaching and Learning?. Second, How is the implementation of Islamic religious education based on Contextual Teaching and Learning?. Third, How is the evaluation of Islamic religious education based on Contextual Teaching and Learning?.This research used qualitative approach. Data collection used interview technique, observation and documentation. The collected data is checked for validity by source triangulation techniques and methods, data checking and peer discussions. Data are analyzed by taking steps; (1) data reduction (2) data presentation and (3) drawing conclusions.The findings of the results of research from the data analysis as follows, during the learning process of Islamic education, teacher as managerial learning has applied the principles of management planning learning Islamic religious education, implementing learning Islamic religious education and conducts evaluation of the implementation of learning Islamic education with contextual teaching and learning strategy.